2023
DOI: 10.1111/jvim.16698
|View full text |Cite
|
Sign up to set email alerts
|

Mineral, trace element, and toxic metal concentration in hair from dogs with idiopathic epilepsy compared to healthy controls

Abstract: Background Altered trace element status is associated with epilepsy in humans and dogs with idiopathic epilepsy (IE). Objectives Compare hair element concentrations in epileptic and healthy dogs. Animals Sixty‐three dogs with IE (53 treated, 10 untreated) and 42 controls. Methods Case‐control study using ICP‐MS to determine hair calcium, magnesium, phosphorus, sodium, potassium, iron, copper, manganese, zinc, selenium, chromium, lead, mercury, cadmium, arsenic, aluminum, and nickel concentration. Groups were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(121 reference statements)
0
0
0
Order By: Relevance
“…Although no association was found between serum copper and epilepsy in the general population, the zinc/copper ratio might offer an alternative perspective for diagnosing and treating epilepsy.An animal study found that the zinc/copper ratio in epileptic dogs was lower than in healthy dogs [31]. This study aligns with research on potential biomarkers in pediatric epilepsy,both showing a negative correlation between zinc/copper and epilepsy [14].…”
Section: Discussionsupporting
confidence: 85%
“…Although no association was found between serum copper and epilepsy in the general population, the zinc/copper ratio might offer an alternative perspective for diagnosing and treating epilepsy.An animal study found that the zinc/copper ratio in epileptic dogs was lower than in healthy dogs [31]. This study aligns with research on potential biomarkers in pediatric epilepsy,both showing a negative correlation between zinc/copper and epilepsy [14].…”
Section: Discussionsupporting
confidence: 85%